Evaluation of a Single-Tube Multiplex Real-Time PCR for Differentiation of Members of the Mycobacterium tuberculosis Complex in Clinical Specimens - Halse, Tanya A. (American Society for Microbiology, 2011)
Members of the Mycobacterium tuberculosis complex (MTBC) differ in virulence attributes, drug resistance patterns, and host preferences. The rapid differentiation of these species to determine zoonotic or human sources of tuberculosis disease or to direct treatment can benefit both public health and patient management. Commercially available assays cannot differentiate these species, and published assays have not been evaluated directly on clinical specimens. A real-time PCR assay for the differentiation of M. tuberculosis, M. bovis, M. bovis BCG, M. africanum, M. microti, and M. canettii was developed. The presence or absence of regions of difference (RD) between the genomes of members of the MTBC allowed for the design of a single-tube five-plex real-time PCR assay to differentiate these species. This assay assesses the presence of RD1, RD4, RD9, RD12, and a region exterior to RD9 which is present in all MTBC members. To evaluate the performance of this assay, 192 clinical specimens positive for MTBC by real-time PCR were tested, resulting in a 94% correlation of the real-time PCR with the identification results obtained with cultured material. Additionally, 727 Bactec MGIT 960-positive cultures were tested, resulting in a 97% concordance between the methods. This real-time PCR is an inexpensive and rapid (2.5-h) method performed in a closed-format system and requiring minimal hands-on time that can be implemented in a clinical laboratory and used directly on clinical specimens.